Sosialisasi Kewirausahaan dan Pendidikan Anak; Antara Bisnis On Line dan Mengasuh di Era Digital - Zain, Nuryetty; Febriantina, Susan; ., Marsofiyati (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2017)
This activity aims to empower tech-savvy citizens to increase family incomes through networked businesses. Besides, this program also empowered people to technically literate children's education in the digital age. Both of the activities are integrated in one program. The activity method used in this program is expected to give ease to the participants of the activity. In this activity, the method used is explanation method, sharing, questioning, case study, discussion and online shop application practice. In the explanatory method, each instructor delivers the related material and planned to make a power point slide and brief activities module to be distributed to the participants of the activity. The results achieved in this activity are 1) the advantage of the activity was very useful for the participants; 2) the participants were also enthusiastic in giving responses during the activity; 3) this activity was supported by some nongovernmental organizations such as the forum of children’ friendly city at Depok (FOKLA Depok) and Tunas Ilmu Foundation. Finally, we can conclude this activity was very useful for the people around.